2019
DOI: 10.32098/mltj.02.2014.04
|View full text |Cite
|
Sign up to set email alerts
|

Motor and cognitive development: the role of karate

Abstract: Background: regular physical activity has an effect on biological responses in both muscles and organs that, in turn, alter the structure and functions of the brain. Therefore, this study aims at comparing motor (sprint, coordination ability and explosive legs strength skills) and cognitive abilities (working memory, attention, executive functioning) in children. Methods: 39 children with average chronological age of 9 years were divided in: Karatekas (n=19) and Sedentary (n=20) groups. Their abilities were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 20 publications
(39 reference statements)
3
60
0
3
Order By: Relevance
“…From an operational standpoint, prolonged sitting at a desk is the type of sedentary behaviour typically observed in the office workplace. Seventy-three percent of the UK population aged 16-64 are currently in employment [4,5] with a large number of these workers in office-related jobs [6]. Studies have identified that the workplace contributes to the majority of excessive daily sitting time in officebased employees [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…From an operational standpoint, prolonged sitting at a desk is the type of sedentary behaviour typically observed in the office workplace. Seventy-three percent of the UK population aged 16-64 are currently in employment [4,5] with a large number of these workers in office-related jobs [6]. Studies have identified that the workplace contributes to the majority of excessive daily sitting time in officebased employees [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings indicate that the athletes who achieve a faster CRT are closer to high-level performance in competitions . A similar conclusion regarding karate athletes has been given by , while a completely different perspective on the importance of RT in karate has been introduced by results of comparison of coordination (Alesi et al, 2014). However, almost none of the studies addressing these issues deal with children of preadolescent and adolescent age.…”
Section: Introductionmentioning
confidence: 70%
“…С тим у вези, деца укључена у програм вежбања каратеа могла би остварити позитивне ефекте када је у питању развој когнитивних функција. Наиме, нека истраживања показују да карате поспешује развој когнитивних функција, укључујући и ВР, брзину обраде информација, радну меморију и визуелно-моторну координацију (Alesi et al, 2014). Међутим, студија које се баве овим проблемима код деце преадолесцентског и адолесцентског узраста, готово да нема.…”
Section: Resultsunclassified
“…In another meta-analysis, pre-adolescent children were found to have increased executive function after one aerobic exercise session (effect size 0.540) [39]. One study investigating karate and its impact on motor and cognitive development showed that this particular martial arts form resulted in improved attention through the Tower of London test (effect size 0.88, p < 0.05) [40]. Martial arts teach children to practice self-control, concentration and meditation that may ultimately result in improvements of executive function.…”
Section: Mind–body Therapiesmentioning
confidence: 99%